2010
DOI: 10.1002/jnr.22538
|View full text |Cite
|
Sign up to set email alerts
|

Expression of macrophage inflammatory protein‐1α and monocyte chemoattractant protein‐1 in glioma‐infiltrating microglia: Involvement of ATP and P2X7 receptor

Abstract: Chemokines can be produced by gliomas, which mediate the infiltration of microglia, a characteristic feature of glioma-associated neuropathogenesis. ATP that is released at a high level from glioma has been reported to play a regulatory role in chemokine production in cultured glioma cells. The objective of this study was to define the potential role of extracellular ATP in the regulation of macrophage inflammatory protein-1α (MIP-1α) and monocyte chemoattractant protein-1(MCP-1) expression in glioma-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 48 publications
4
39
0
1
Order By: Relevance
“…6A). It is reported that P2X 7 receptors could regulate the expression of MCP-1, 28,29 which plays a key role in the recruitment of progenitor cells. 30 So, we also detected the expression of MCP-1 in BBG treated or untreated group.…”
Section: P2x 7 Receptors Inhibition Suppressing the Homing Of Transplmentioning
confidence: 99%
“…6A). It is reported that P2X 7 receptors could regulate the expression of MCP-1, 28,29 which plays a key role in the recruitment of progenitor cells. 30 So, we also detected the expression of MCP-1 in BBG treated or untreated group.…”
Section: P2x 7 Receptors Inhibition Suppressing the Homing Of Transplmentioning
confidence: 99%
“…ED1, which is mainly found in phagocytosing macrophages and reactive microglia, is a lysosomal membrane protein. Macrophages with ED1 can be observed in the majority of brain tumors, as well as in gliomas (18). Cluster of differentiation 8 (CD8) was traditionally recognized as a marker that is mainly expressed in cytotoxic T cells and natural killer cells (19 (21).…”
Section: Introductionmentioning
confidence: 99%
“…P2X7 receptor agonists produced cell death in the glioma radiosensitive cell line M059J, but the radioresistant glioma cell line, U138-MG, presented resistance to death when treated with either ATP or BzATP [598]. ATP released from glioma tumour cells may act as the regulator, via P2X7 receptor signalling, that increases macrophage inflammatory protein-1α and monocyte chemoattractant protein-1 expression in tumour-infiltrating microglia [599]. It was claimed that BzATP-mediated calcium signalling in C6 cells was mediated by P2Y (perhaps P2Y 2 ), rather than P2X7 receptors [36].…”
Section: Gliomasmentioning
confidence: 99%